ICU rehabilitation and outcomes in elderly pelvic ring fractures due to high-energy trauma - Kenta Momii; Hiroki Yagi; Tomoyuki Nezu; Kanji Ohsaki; Chen Man; Takahiro Tajimi; Takeshi Iyonaga; Masaaki Nishihara; Yuji Shono; Jun Maki; Tomohiko Akahoshi; Yasuharu Nakashima (Japanese Society of Physical Fitness and Sports Medicine, 2024)
Pelvic fractures, accounting for 2-8% of skeletal injuries, present a significant burden in patients with trauma. High-energy incidents often result in severe pelvic trauma accompanied by comorbidities leading to high mortality rates. Managing these complications adds complexity to the treatment process, particularly in older patients who experience longer recovery times and higher injury severity. To improve the long-term quality of life, a multidisciplinary approach is essential. However, rehabilitation feasibility is influenced by the patient's condition and pelvic fixation stability, necessitating individualized treatment. This study investigated the rehabilitation status and long-term outcomes of older patients with severe polytrauma and pelvic ring fractures caused by high-energy trauma. The results revealed that 79.2% of the patients achieved full weight-bearing, with a median time of 41.5 days, and eventually 58.3% were discharged home. Complications were observed in 83.3% of the patients, with various challenges affecting successful home discharge. Multidisciplinary rehabilitation programs are promising for optimizing outcomes and facilitating recovery in vulnerable patient populations. Still, larger, more focused studies are needed to gain more comprehensive insights into the treatment and recovery of older patients with pelvic ring fractures and severe polytrauma. Understanding these factors is crucial for guiding clinical decision-making and improving long-term outcomes in this population.